RESPON PH TANAH TERHADAP APLIKASI KAPUR PERTANIAN PADA BIBIT KELAPA SAWIT (Elaeis Guineensis Jacq) FASE MAIN NURSERY - Riyan Riyan; Nurlia Husna Siregar; Niza Azzhara; Pandu Setio; Anna Kusumawati (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2026)
This study aimed to determine the effect of different doses of agricultural lime (dolomite) on changes in the pH of peat soil used as a growing medium for oil palm seedlings during the main nursery phase. Peat soil generally has a high level of acidity, which can limit the availability of nutrients for plant growth. The experiment was conducted using a non-factorial Completely Randomized Design (CRD) with five dolomite dosage treatments, namely 0 g (control), 20 g, 50 g, 70 g, and 100 g per polybag, each replicated 12 times. Soil pH observations were carried out daily for 9 days after dolomite application. The data were analyzed using Analysis of Variance (ANOVA), followed by Duncan Multiple Range Test (DMRT) at a 5% significance level, as well as Pearson Correlation Test to determine the relationship between dolomite dosage and soil pH changes. The results showed that dolomite application significantly increased soil pH. The treatment with 100 g/polybag produced the highest average pH value of 6.46, while the control treatment only reached a pH of 5.73. In addition, a significant positive correlation (r = 0.556) was found between increasing dolomite dosage and soil pH improvement. Therefore, the application of agricultural lime proved effective in increasing and stabilizing peat soil pH, making it more suitable as a growing medium for oil palm nurseries.